A four-terminal-pair Josephson impedance bridge combined with a graphene-quantized Hall resistance. (31st March 2021) - Bauer, S; Behr, R; Elmquist, R E; Götz, M; Herick, J; Kieler, O; Kruskopf, M; Lee, J; Palafox, L; Pimsut, Y; Schurr, J
Abstract: This paper introduces a four-terminal-pair impedance bridge based on pulse-driven Josephson junctions arrays which is designed to link any kind of impedance to the quantized Hall resistance. The unique features of the quantized Hall resistance in a multiple series connection allows to dispense a combining network and leads to a compact and simple design of the whole setup. Moreover, the low noise of a quantized Hall resistance reduces the measurement time compared to resistance standards at room temperature which is essential for the characterization of quantum Hall devices in the AC regime. A first measurement campaign confirmed the expected low noise of 1.82 n V / H z for a link to a 10 nF capacitance standard. The repeatability of the bridge was found to be few parts in 10 8 . Capacitance and resistance standards were measured at 1233.15 Hz against graphene based quantum Hall resistance devices.